The Pulmonary Thromboendarterectomy Increases Gradually All Over the World; Review - (:unkn) unknown (My University, 2016)
Pulmoner tromboendarterektomi (PTE) kronik tromboembolik pulmoner hipertansiyonda hemodinamik ve fonksiyonel iyileşmeyi sağlayan karmaşık bir cerrahi işlemdir. PTE işlemi uygulaması tüm dünyada giderek yaygınlaşmakta ve cerrahi deneyim arttıkça ölüm oranları her geçen gün giderek azalmaktadır. Başlangıçta %4 -24 gibi yüksek değerlerde olan cerrahi ölüm oranları tüm dünyada önemli oranda düşmüştür. PTE pulmoner arterleri tıkayan ve erimemiş olan trombotik tıkacı çıkarmayı amaçlayan cerrahi bir tekniktir. Kronik tromboemboliye bağlı pulmoner hipertansiyon olgularında PTE işlemi sonrası pulmoner arter basıncı ve pulmoner vasküler dirençte önemli ve sürekli değişiklikler gözlenmektedir. Son günlerde, daha önceden cerrahi işlem için uygun olmadığı düşünülen bazı olgulara bile artık PTE önerilmektedir.

Pulmonary endarterectomy (PTE) is a complex surgical procedure that provides functional and haemodynamic improvement in patients with chronic thromboembolic pulmonary hypertension. The use of PTE procedures is increasing all over the world and by getting a high level of surgical expertise; therefore, mortality rates are gradually decreasing day by day. Initially, operative mortality rates were high with a range of approximately 4%-24%. These rates have substantially decreased all over the world. PTE is a surgical technique that aims to remove unresolved thromboembolic material that obstructs the pulmonary arteries. Significant and persistent decreases in pulmonary artery pressures and pulmonary vascular resistance are observed in patients with chronic thromboembolic pulmonary hypertension after the surgery. Nowadays, this operation is offered to those patients who were considered to be inoperable in the past.
Pulmoner Tromboendarterektomi Tüm Dünyada Giderek Yaygınlaşmaktadır; Derleme
Keywords: Cerrahi